A preliminary study on the average yield of crude capsaicin from common varieties of Capsicum frutescens L. at two stages (Young and mature) using three extracting solvent. - Cadornigara, Ma. Sylvia C.
Crude capsaicin content of the air dried and homogenized plant material of the three varieties of Capsicum frutescens L. namely cayenne, tobasco and `kitikot' were determined using diethyl ether, 99.5 ethanol and 1.0N NaOH as extracting reagents. Statistical analysis showed no significant difference on the average percent yield of crude capsaicin on the three varieties of capsicum frutescens L. using similar extracting solvent, but a significantly yield of crude capsaicin was found with 99.5 ethanol extracts identified could probably be capsaicinoids (Rf 15-17), carotenoids (only in 99.5 ethanol, Rf 96-97), and capsaicin (Rf 27-29) using n-hexane-acetone.